2000
DOI: 10.1182/blood.v95.1.102.001k25_102_110
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of human cord blood CD34+CD38−cells in ex vivo culture during retroviral transduction without a corresponding increase in SCID repopulating cell (SRC) frequency: dissociation of SRC phenotype and function

Abstract: Current procedures for the genetic manipulation of hematopoietic stem cells are relatively inefficient due, in part, to a poor understanding of the conditions for ex vivo maintenance or expansion of stem cells. We report improvements in the retroviral transduction of human stem cells based on the SCID-repopulating cell (SRC) assay and analysis of Lin− CD34+CD38−cells as a surrogate measure of stem cell function. Based on our earlier study of the conditions required for ex vivo expansion of Lin−CD34+ CD38− cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
2
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 46 publications
3
31
2
1
Order By: Relevance
“…Analysis of SEP shows that input cells that have been expanded for 14 d have a greater potential for total cell production and specific generation of CD34 1 and CD19 1 cells than either cells expanded for 7 d or unexpanded cells. Our results are in contrast to those described by Novelli et al (1999), who showed that SEP decreased in cells that had been expanded for 7 d. Their observed decrease in SEP may have been related to the fact that the mice were sacrificed at different time intervals post transplant, some animals received intraperitoneal cytokines post transplant, and other mice were transplanted with cells that had been expanded with five growth factors in media containing FCS, which is known to promote differentiation and reduce expansion potential (Dorrell et al, 2000). Analysis of SEP evaluates the clinical efficacy of the CD34 1 cells put into the cytokine culture and provides an indication of the in vivo generation potential of these cells for the production of myeloid and megakaryocytic precursors.…”
Section: Discussioncontrasting
confidence: 99%
“…Analysis of SEP shows that input cells that have been expanded for 14 d have a greater potential for total cell production and specific generation of CD34 1 and CD19 1 cells than either cells expanded for 7 d or unexpanded cells. Our results are in contrast to those described by Novelli et al (1999), who showed that SEP decreased in cells that had been expanded for 7 d. Their observed decrease in SEP may have been related to the fact that the mice were sacrificed at different time intervals post transplant, some animals received intraperitoneal cytokines post transplant, and other mice were transplanted with cells that had been expanded with five growth factors in media containing FCS, which is known to promote differentiation and reduce expansion potential (Dorrell et al, 2000). Analysis of SEP evaluates the clinical efficacy of the CD34 1 cells put into the cytokine culture and provides an indication of the in vivo generation potential of these cells for the production of myeloid and megakaryocytic precursors.…”
Section: Discussioncontrasting
confidence: 99%
“…And to this purpose, we followed well-defined, standard criteria. However, it has been shown that the relationship of stem cell immunophenotype and function is altered when primitive hematopoietic cells are cultured in serum-free liquid suspension cultures [33,35,50]. Thus, it is possible that when selecting the cell populations generated in vitro, we were gating-out cells that possess functional capacities related to HSCs and progenitor cells, but whose immunophenotypes do not correspond to those considered as standard phenotypes of HSCs and HPCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, to the best of our knowledge, this hypothesis has not been conclusively demonstrated. In fact, there is extensive evidence indicating that when primitive hematopoietic cells are cultured in vitro, they experience a variety of phenotypic and functional changes induced by the culture conditions, including a tendency of HSCs to lose their stemness when they enter cell cycle, and an external pressure on HPCs to mature [33][34][35]. Thus, even though they may retain their original immunophenotype after ex vivo expansion, their genomic and functional integrity may be altered.…”
Section: Introductionmentioning
confidence: 99%
“…This view is supported by the loss of more mature CFC to the MACS negative fraction whereas most of the LTC-IC were retained in the MACS positive fraction. There is also evidence that the CD38 antigen may be lost from CD38 positive cells during expansion culture, leading to falsely high estimates of CD38 ¹ cell expansion (Dorrell et al, 1998).…”
Section: Discussionmentioning
confidence: 99%